Association between circulating fibroblast growth factor‐23 and age‐related cardiovascular–renal parameters in a healthy Chinese population. Issue 8 (18th July 2016) - Wang, Nan; Bai, Xiaojuan; Jin, Bo; Han, Wen; Sun, Xuefeng; Chen, Xiangmei
Abstract : Aim: Previous studies showed that circulating fibroblast growth factor‐23 (FGF23) is a new biomarker linked to cardiovascular and kidney diseases. Here, we explored the association between serum FGF23 and aging‐related cardiovascular–renal parameters in a healthy Chinese population. Methods: A total of 314 healthy participants aged 36–87 years were enrolled. Cardiovascular structure and function were assessed by the left ventricular ejection fraction, the ratio of early diastolic peak flow velocity to late diastolic peak flow velocity at the mitral leaflet tips, carotid intima‐media thickness, the diameter of the bilateral common carotid artery, blood systolic peak and end diastolic velocities, which were measured by M‐mode ultrasonography. Glomerular filtration rate was evaluated using the Chronic Kidney Disease Epidemiology Collaboration equation and Chronic Kidney Disease Epidemiology Collaboration equation for Asians. Serum FGF23, 1, 25‐dihydroxy vitamin D3 and parathyroid hormone were measured by enzyme‐linked immunosorbent assay. Results: For all participants, intima‐media thickness/diameter of the bilateral common carotid artery gradually decreased with the progression from low to high FGF23 concentration ( P  < 0.05). After adjusting for all possible confounders, FGF23 remained significantly associated with intima‐media thickness/diameter of the bilateral common carotid artery ( P  = 0.016). In women, serum FGF23 was significantly associated with serum creatinine, cystatin C and estimated glomerular filtration rate in the Spearman correlation analysis. FGF23 remained significantly associated with serum creatinine ( P  = 0.046) and estimated glomerular filtration rate ( P  = 0.034) after full adjustment. However, no such relationship was apparent in men. Conclusions: Serum FGF23 was correlated with aging‐related cardiovascular–renal parameters even in healthy people. Measurement of serum FGF23 can provide valuable information to predict cardiovascular–renal function in healthy people, especially in older female adults.Geriatr Gerontol Int 2017; 17: 1221–1231 .